An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Emerging advanced technologies: Modulation of sensory properties in milk and whey systems – A review - Waris Aziz; Khawaja Muhammad Ali Tayyab; Tahir Mahmood Qureshi; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Trends in Food Science & Technology, 2026)

Stability analytical solution for the geosynthetic-reinforced pile-supported embankments based on an improved three-wedge model - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Hanyan Gu; Yanjun Qiu (Geotextiles and Geomembranes, 2026)

Hydrolyzed konjac glucomannan retards egg white protein digestion via glycosylation -driven gastric texture and rheology modulation - Lulu Guo; Yicheng Guo; Yating Wu; Shende Hu; Xiaosan Wang; Luping Gu; Cuihua Chang; Junhua Li; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2026)

pH-Shifting combined with heat treatment regulates the aggregate structure and interfacial functional properties of egg white protein microparticles powder - Yating Wu; Yicheng Guo; Junhua Li; Luping Gu; Yanjun Yang; Cuihua Chang; Yujie Su (Food Research International, 2026)

Egg yolk phospholipid peptides as dual-functional nanocarriers for curcumin: Enhanced hypolipidemic effects and mechanism - Ruyi Zhang; Wenhui Feng; Lili Jiang; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Yi Wang; Junhua Li (Food Research International, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Glycyrrhizin-modified mung bean protein for synergistic co-encapsulation of curcumin and naringenin with enhanced stability and bioavailability - Wei Sun; Jiahe Miao; Yanjun Wei; Xianggen Wu; Chenchen Gu (Innovative Food Science & Emerging Technologies, 2026)

Harnessing Lactiplantibacillus plantarum LW11: A promising bio-preservative for extending cake shelf life through antifungal metabolites - Xuechun Wang; Zhishuo Zhang; Cuihua Chang; Yujie Su; Luping Gu; Yanjun Yang; Hong Sun; Junhua Li (Food Control, 2026)

Correction to: Evaluating carbon footprint calculators: a comprehensive assessment framework - Ziqian Xia; Kuang Liu; Jiangnan Li; Yanjun Gu; Bo Hu; Yun Zhong; Jinquan Ye; Ka Leung Lam (Clean Technologies and Environmental Policy, 2026)

Sediment sink-source shifts drive intensified internal phosphorus (P) release during the rainy season in a eutrophic plateau lake - Chaoran Guo; Fu Zhang; Yanjun Wu; Chengfei Tong; Yuyi Wang; Jianxia Cai; Zheng Zhao; Jinliang Liu; Qi Yang; Xiaozhi Gu; Jicheng Zhong; Jizheng Pan (Water Research, 2026)

Enzyme and thermal induced transition of egg white proteins from dense-globular to random coil triggering uniform microparticle formation - Zhishuo Zhang; Yi Wang; Ruyi Zhang; Xuechun Wang; Junhua Li; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang (Food Research International, 2026)

Glacier and glacial lake evolution in response to local climate forcing: A quantitative assessment in Ulugh Muztagh, Eastern Kunlun Mountains - Lihua Chen; Yanjun Che; Yun Cao; Mingjun Zhang; Lailei Gu; Shijin Wang (Cold Regions Science and Technology, 2026)

High internal-phase pickering emulsions stabilized by mung bean protein–glycyrrhizin complexes for β-carotene delivery - Haoling Yang; Bing Wang; Yanjun Wei; Chenchen Gu; Xianggen Wu (Food Chemistry, 2025)

Egg yolk phospholipid peptide-dihydromyricetin nano-composites: Temperature-driven assembly and evaluation of stability and pharmacokinetics - Yingxin Wei; Jinping Zhang; Wenhui Feng; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

Exploring the potential impact of GPC-enriched egg yolk derivatives on cognitive vitality in aging brains: A preliminary study - Wen Yu; Qing Gao; Yanjun Yang; Cuihua Chang; Wei Hu; Yujie Su; Luping Gu; Junhua Li (Food Bioscience, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Effect of egg yolk component and its enzymatic hydrolysate on the flavor and texture of walnut cake - Tingting Tang; Qing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Effects of enzyme treatment on structural characteristics of egg yolk, plasma and granule and their correlation with flavor components - Tingting Tang; Wen Yu; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2025)

Genome and transcriptome analysis provide insights into the genetics and breeding of Salix suchowensis growth traits - Wei Liu; Shaobo Gu; Mingjia Zhu; Yu Han; Xiaogang Dai; Huaitong Wu; Tongming Yin; Linjie Guo; Landi Feng; Yanjun Zan; Jianquan Liu (New Forests, 2025)

Evaluating carbon footprint calculators: a comprehensive assessment framework - Ziqian Xia; Kuang Liu; Jiangnan Li; Yanjun Gu; Bo Hu; Yun Zhong; Jinquan Ye; Ka Leung Lam (Clean Technologies and Environmental Policy, 2025)

Cysteine and dialysis mediated inhibition of dynamic changes in glycosylated egg white protein during storage - Lulu Guo; Wanqiu Zhang; Fan Zhang; Shende Hu; Qianwen Zhao; Cuihua Chang; Junhua Li; Zijian Huang; Luping Gu; Yanjun Yang; Yujie Su (Food Chemistry, 2025)

Effect of adding different egg yolk oil on the flavor and physicochemical properties of mayonnaise - Xuejing Gao; Tingting Tang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Production of glycerylphosphorylcholine-enriched defatted egg yolk powder through integrated enzymatic and supercritical CO2 processing - Wen Yu; Luping Gu; Cuihua Chang; Yujie Su; Yi Wang; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

Melatonin attenuates inflammatory bone loss by alleviating mitophagy and lactate production - Zexin Lin; Yuan Gu; Yingsong Liu; Zilin Chen; Shuai Fang; Zhuan Wang; Zixian Liu; Qingrong Lin; Yanjun Hu; Nan Jiang; Bin Yu; Guanqiao Liu (Apoptosis, 2025)

The role of defatted hydrolyzed egg yolk powder in protecting DHA algal oil - Yingxin Wei; Huan Rui; Xuechun Wang; Cuihua Chang; Yi Wang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Chemistry, 2025)

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

3D printing food flow in different extruders based on crazy and adaptive salp swarm algorithm-deep extreme learning machine improved-lattice Boltzmann method - Weiwei Wu; Minheng Gu; Xin Liu; Zhongyi Shan; Shuang Ding; Yanjun Zhang; Wenhan Yang (Journal of Food Engineering, 2025)

Effect of enzymatic hydrolysis on flavor enhancement of yogurt fermented by lactic acid bacteria in egg white - Qing Gao; Ruolin Xu; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Bioscience, 2025)

Numerical study of regular wave dynamics for optimizing coral reef restoration - Jiuming Han; Yanjun Li; Xizeng Zhao; Tao Liu; Yanzhen Gu; Shuangyan He; Peiliang Li; Ruili Sun (Ocean Engineering, 2025)

Characterization of liquid egg yolks hydrolyzed by phospholipase: Structure, thermal stability and emulsification properties - Ruolin Xu; Qing Gao; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Research International, 2024)

Extraction of egg yolk lipids via salt-induced synergistic heat treatment: Fabrication, characterization and flavor analysis - Xuejing Gao; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Effects of non-covalently bound polyphenols/vitamins on the structure and functional characteristics of egg yolk powder - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Development of egg yolk lipoprotein hydrolysate for nano-delivery of curcumin: Structure-function relationship - Lili Jiang; Yanjun Yang; Yujie Su; Cuihua Chang; Luping Gu; Chunfang Liu; Junhua Li (Innovative Food Science & Emerging Technologies, 2024)

Differential effects of egg consumption on fecal lipid metabolism: Insights from C57BL/6J mice under chow diet and high-fat diet - Fan Zhang; Tian Yang; Junhua Li; Luping Gu; Cuihua Chang; Li Yang; Zijian Huang; Yujie Su; Yanjun Yang (Food Bioscience, 2024)

Investigation into the impact of enzyme treatment on the structural characteristics of egg yolk protein and its correlation with flavor constituents - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Development of a novel dual-enzyme modification method for the functionality improvement of egg yolk powder - Huan Rui; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Design and Analysis of a Buoy-Based Cable Seafloor Observatory System Response under Extreme Weather Conditions - Wenjie Zhou; Yanjun Li; Yulu Zhang; Qingyan Jiang; Dong Chen; Yanzhen Gu; Yuan Lin (Journal of Marine Science and Engineering, 2024)
In order to address the requirements of scientific multidisciplinary observation in diverse small-scale regions, we have introduced the Buoy-based Cable Seafloor Observatory System (BCSOS). This system offers a distinct advantage in contexts where the use of shorter cables is feasible, contrasting with the lengthy cables typically necessary for conventional observatories. The BCSOS consists of three primary components: the Real-Time Electric Communication (RTEC) Buoy, the Power Information Transmission System (PITS), and the Seafloor Observation Subsystem (SOS). The RTEC Buoy is equipped with instruments for measuring sea surface parameters and serves as a data and power hub. The PITS, comprising a robust EM cable, connects the buoy to the SOS, which houses instruments for seafloor observations. The system is designed for a maximum water depth of 100 m and has an expected lifespan of about 5 years. The BCSOS prototypes were deployed at the Huangqi Peninsula, Fujian Province, and successfully documented the process during Typhoon Doksuri (international code 2305) at the end of July 2023. The recorded data from the BCSOS revealed a significant increase in wave height and period as the storm approached the Huangqi Peninsula. Additionally, the RTEC buoy exhibited a notable response to the large waves. The data analysis revealed a distinct pattern between the buoy response and the direction of wave propagation across various sea conditions, that the buoy’s angular movement in pitch and roll directions follows a regular elliptical distribution corresponding to different wave propagation directions. Upon thorough evaluation, future enhancements to the system are slated to concentrate on refining its design, with a particular emphasis on bolstering stability and enhancing corrosion resistance. These improvements are aimed at cementing the system’s long-term viability and performance within the challenging marine environment.

Achieving the supply-demand balance of ecosystem services through zoning regulation based on land use thresholds - Xiaoqing Zhao; Yifei Xu; Junwei Pu; Junyi Tao; Yanjun Chen; Pei Huang; Xinyu Shi; Yuju Ran; Zexian Gu (Land Use Policy, 2024)

Fabrication of phosphatidylcholine-EGCG nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in a Caco-2 monolayer model - Mengya Zhang; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Chemistry, 2024)

Insight into the effects of different ripeness levels on the quality and flavor chemistry of Noni fruit (Morinda citrifolia L.) - Xiaoai Chen; Chunhe Gu; Kexue Zhu; Fei Xu; Zhen Feng; Yanjun Zhang (Food Chemistry, 2024)

Effects of cholesterol removal treatment on the flavor and physicochemical properties of hot gel egg yolk - Tingting Tang; Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Differences in the gelation, digestibility and release of antioxidant peptides of egg white/yolk in boiled eggs - Min Zhu; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Stability analysis of unsaturated soil slopes with cracks under rainfall infiltration conditions - Lei Zhang; Xin Jiang; Rong Sun; Hanyan Gu; Yongguo Fu; Yanjun Qiu (Computers and Geotechnics, 2024)

Unexpected associations of long-term and excessive exposure to trivalent chromium with hypertension and glycosuria in male tannery workers - Tomoyuki Tsuchiyama; Dijie Chen; M.M. Aeorangajeb Al Hossain; Akira Tazaki; Takumi Kagawa; Yishuo Gu; Yanjun Gao; Fitri Kurniasari; Nazmul Ahsan; Anwarul A. Akhand; Masashi Kato (Chemosphere, 2023)

Fabrication of egg white protein/phosphatidylcholine-EGCG co-assembled nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in Caco-2 cultures - Mengya Zhang; Xuejing Gao; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Hydrocolloids, 2023)

Combined effect of heating and enzymatic hydrolysis on the dispersibility and structure properties of egg white powder - Tingting Wang; Cuihua Chang; Wanying Cheng; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Journal of Food Engineering, 2023)

Thermal gelation and digestion properties of hen egg white: Study on the effect of neutral and alkaline salts addition - Junhua Li; Weijian Zhang; Tingting Tang; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Food Chemistry, 2023)

Influence of selected gums on the foaming properties of egg white powders: Kinetics of foam formation and baking performance - Junhua Li; Jinjing Sun; Cuihua Chang; Luping Gu; Yujie Su; Jiali Zhai; Yanjun Yang (Food Hydrocolloids, 2023)

Foaming properties of dried egg white at different outlet temperatures - Junhua Li; Jinjing Sun; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Journal of Food Engineering, 2023)

Sugar alcohols as cryoprotectants of egg yolk: Inhibiting crystals and interactions - Haosheng Zhu; Junhua Li; Yujie Su; Luping Gu; Cuihua Chang; Yanjun Yang (Journal of Food Engineering, 2023)

Effects of hydroxylation at C3′ on the B ring and diglycosylation at C3 on the C ring on flavonols inhibition of α-glucosidase activity - Yajuan Qin; Xiaoai Chen; Fei Xu; Chunhe Gu; Kexue Zhu; Yanjun Zhang; Gang Wu; Ping Wang; Lehe Tan (Food Chemistry, 2023)

Characterization of physical properties, volatile compounds and aroma profiles of different salted egg yolk lipids - Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Wen Xiong; Yujie Su; Yanjun Yang (Food Research International, 2023)

Contribution of five major apple polyphenols in reducing peanut protein sensitization and alleviating allergencitiy of peanut by changing allergen structure - Shanfeng Sun; Tianyi Jiang; Yanjun Gu; Lu Yao; Hang Du; Jiangzuo Luo; Huilian Che (Food Research International, 2023)

Gel properties of soy protein isolate-potato protein-egg white composite gel: Study on rheological properties, microstructure, and digestibility - Yuanqi Lv; Lilan Xu; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Ming Zhang; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2023)

Do behavioural interventions enhance waste recycling practices? Evidence from an extended meta-analysis - Ziqian Xia; Yanjun Gu; Jiangnan Li; Jinliang Xie; Fangyi Liu; Xing Wen; Xi Tian; Chao Zhang (Journal of Cleaner Production, 2023)

Scalable, large-size, and flexible transparent bamboo - Kaili Wang; Haozhe Peng; Qiyu Gu; Xinzhi Zhang; Xiaorong Liu; Youming Dong; Yahui Cai; Yanjun Li; Jianzhang Li (Chemical Engineering Journal, 2023)

Immunomodulatory Function of Egg White Peptides in RAW264.7 Macrophage Cells and Immunosuppressive Mice Induced by Cyclophosphamide - Fan Zhang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (International Journal of Peptide Research and Therapeutics, 2022)

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Hypoxia preconditioning improves structure and function of astrocytes mitochondria via PGC-1α/HIF signal - Yue Wu; Cunlin Gu; Lu Huang; Yuanqing Zhao; Yanjun Tang; Hongqian Zhao; Qiong Wu (Journal of Biosciences, 2021)

Thermal deterioration of high-temperature granite after cooling shock: multiple-identification and damage mechanism - Yanjun Shen; Xin Hou; Jiangqiang Yuan; Zhenhao Xu; Jianshuai Hao; Linjun Gu; Zhiyun Liu (Bulletin of Engineering Geology and the Environment, 2020)

Expression profile of circular RNAs in myocardial ischemia/reperfusion with and without intermittent hypobaric hypoxia preconditioning - Jiliang Tan; Shanshan Gu; Yanjun Zheng; Huangtian Yang (Science China Life Sciences, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Transcriptome analysis reveals that constant heat stress modifies the metabolism and structure of the porcine longissimus dorsi skeletal muscle - Yue Hao; Yuejin Feng; Peige Yang; Yanjun Cui; Jiru Liu; Chunhe Yang; Xianhong Gu (Molecular Genetics and Genomics, 2016)

Risk factors of severe hand, foot and mouth disease complicated with cardiopulmonary collapse - Chunlan Song; Cheng Yibing; Yanjun Guo; Zhipeng Jin; Yajie Cui; Xue Gu (Infectious Diseases, 2015)

Analysis of molecular variation of porcine reproductive and respiratory syndrome virus in Central China from 2006 to 2012 - Yuejun Shi; Zhibin Hu; Zhenghui Xiong; Yanjun Zhou; Xin Jin; Changqin Gu; Xueying Hu; Guofu Cheng; Nianhua Song; Wanpo Zhang (Archives of Virology, 2013)